2014
DOI: 10.3892/mmr.2014.2401
|View full text |Cite
|
Sign up to set email alerts
|

SCN5A mutations and polymorphisms in patients with ventricular fibrillation during acute myocardial infarction

Abstract: Mutations in the SCN5A gene encoding the Nav1.5 channel α-subunit are known to be risk factors of arrhythmia, including Brugada Syndrome and Long QT syndrome subtype 3. The present study focused on the role of SCN5A variants in the development of ventricular fibrillation (VF) during acute myocardial infarction (AMI). Since VF during AMI is the major cause of sudden death in the Western world, SCN5A mutations represent genetic risk factors for sudden death. By exon re-sequencing, the entire coding region and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…It must be considered that a nonsense mutation can alter a channel protein more seriously than some other kinds of mutations. In fact, the Na V 1.5 protein displays some domains that are critical for protein function; one of these is the voltage sensor domain, which is localized close to exon 9, which maps the mutation described herein [37]. Taken together, all these data provide convincing evidence that a heterozygous state for the c.1111C>T variant in the SCN5A gene can predispose the carrier to BrS.…”
Section: Discussionsupporting
confidence: 55%
“…It must be considered that a nonsense mutation can alter a channel protein more seriously than some other kinds of mutations. In fact, the Na V 1.5 protein displays some domains that are critical for protein function; one of these is the voltage sensor domain, which is localized close to exon 9, which maps the mutation described herein [37]. Taken together, all these data provide convincing evidence that a heterozygous state for the c.1111C>T variant in the SCN5A gene can predispose the carrier to BrS.…”
Section: Discussionsupporting
confidence: 55%
“…A genome wide association study (GWAS) in the AGNES study cohort revealed a strong association between VF during AMI and a gene locus near the CXADR gene, that encodes for the coxsackie- and adenovirus receptor (20). Smaller studies point at genetic variations in the SCN5A gene, coding for the cardiac sodium channel Na v 1.5, as a predisposing factor for the development of VF upon AMI (21). Epidemiology and genetics of VF in AMI have been reviewed recently by Glinge et al (22).…”
Section: Acute Myocardial Infarction and Sudden Cardiac Deathmentioning
confidence: 99%
“…Small studies tested the role of rare variants in arrhythmia-susceptibility genes and suggested a role for SCN5A rare variants. 59,60 Other studies evaluated the role of candidate SNPs. Specifically, NOS1AP variants were associated with higher risk for SCD in white adults 61 ; an association confirmed in the Rotterdam Study, which however did not exclusively include AMI.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%